Public Incentives, Market Motivations, and Contaminated Properties: New Public Management and Brownfield Liability Reform. (19th December 2014) - Eckerd, Adam; Heidelberg, Roy L.
Abstract Brownfields pose challenges to both communities and policy makers. Public funds are insufficient to remediate these contaminated sites, but, given the uncertainty of contamination and the complexity of liability, private interests are reluctant to become involved for fear of future litigation. From a New Public Management perspective, market incentives can be used to encourage private sector remediation of sites. However, this change implies a shift in administrative function from regulation to "getting the incentives right." In this research, the authors investigate whether state and federal reforms aimed at increasing private sector involvement have actually done so, and they consider the implications for other goals of brownfield remediation, such as providing economic development assistance in communities where such change is needed. Findings show that developers respond to insurance and tax incentives, but the authors question whether public incentives are making unattractive redevelopment opportunities worth investing in or simply making profitable redevelopment opportunities more profitable.